Development, In-Vitro Characterization and In-Vivo Osteoinductive Efficacy of a Novel Biomimetically-Precipitated Nanocrystalline Calcium Phosphate With Internally-Incorporated Bone Morphogenetic Protein-2 - Xu, Gaoli; Shen, Chenxi; Lin, Haiyan; Zhou, Jian; Wang, Ting; Wan, Ben; Binshabaib, Munerah; Forouzanfar, Tymour; Xu, Guochao; Alharbi, Nawal; Wu, Gang (Frontiers in Bioengineering and Biotechnology, 2022)
The repair of large-volume bone defects (LVBDs) remains a great challenge in the fields of orthopedics and maxillofacial surgery. Most clinically available bone-defect-filling materials lack proper degradability and efficient osteoinductivity. In this study, we synthesized a novel biomimetically-precipitated nanocrystalline calcium phosphate (BpNcCaP) with internally incorporated bone morphogenetic protein-2 (BpNcCaP+BMP-2) with an aim to develop properly degradable and highly osteoinductive granules to repair LVBDs. We first characterized the physicochemical properties of the granules with different incorporation amounts of BMP-2 using scanning electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. We evaluated the cytotoxicity and cytocompatibility of BpNcCaP by assessing the viability and adhesion of MC3T3-E1 pre-osteoblasts using PrestoBlue assay, Rhodamine-Phalloidin and DAPI staining, respectively. We further assessed the in-vivo osteoinductive efficacy in a subcutaneous bone induction model in rats. In-vitro characterization data showed that the BpNcCaP+BMP-2 granules were comprised of hexagonal HA with an average crystallite size ranging from 19.7-25.1 nm and a grain size at 84.13±28.46 nm. The vickers hardness of BpNcCaP was 32.50±3.58 HV 0.025. BpNcCaP showed no obvious cytotoxicity and was favorable for the adhesion of pre-osteoblasts. BMP-2 incorporation rate could be as high as 65.04±6.01%. In-vivo histomorphometric analysis showed that the volume of new bone induced by BpNcCaP exhibited a BMP-2 amount-dependent increasing manner. The BpNcCaP+50 μg BMP-2 exhibited significantly more degradation and fewer foreign body giant cells in comparison with BpNcCaP. These data suggested a promising application potential of BpNcCaP+BMP-2 in repairing LVBDs.